Tissemouminites: A new group of primitive achondrites spanning the transition between acapulcoites and winonaites. (28th December 2022) - Stephant, A.; Carli, C.; Anand, M.; Néri, A.; Davidson, J.; Pratesi, G.; Cuppone, T.; Greenwood, R. C.; Franchi, I. A.
Abstract: The Northwest Africa (NWA) 090 meteorite, initially classified as an acapulcoite, presents petrological, chemical, and isotopic characteristics comparable to a group of seven primitive winonaites: Dhofar 1222, NWA 725, NWA 1052, NWA 1054, NWA 1058, NWA 1463, and NWA 8614. Five of these samples were previously classified as acapulcoites or ungrouped achondrites before being reclassified as winonaites based on their oxygen isotopic compositions. These misclassifications are indicative of the particular compositional nature of these primitive achondrites. All contain relict chondrules and a lower closure temperature of metamorphism of 820 ± 20 °C compared to other typical winonaites, as well as mineral elemental compositions similar to those of acapulcoites. The oxygen isotopic signature of these samples, δ 17 O of 1.18 ± 0.17‰, δ 18 O of 3.18 ± 0.30‰, and Δ 17 O of −0.47 ± 0.02, is in fact resolvable from both acapulcoites and winonaites. We investigate the relationship between these eight primitive achondrites, typical winonaites, and acapulcoites, to redefine petrological, mineralogical, and geochemical criteria of primitive achondrite classification. Distinguishing between winonaites, acapulcoites, and this group of eight primitive achondrites can be unambiguously done using a combination of several mineralogical and chemical criteria. A combination of olivine fayalite content and FeO/MnO ratio, as well as plagioclase potassium content allow us to separate these three groups without the absolute necessity of oxygen isotope analyses. NWA 090 as well as the other seven primitive achondrites, although related to winonaites, are most likely derived from a parent body distinct from winonaites and acapulcoites–lodranites, and define a new group of primitive achondrites that can be referred to as tissemouminites.